2022
DOI: 10.1101/2022.04.20.488959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yield-Stress and Creep Control Depot Formation and Persistence of Injectable Hydrogels Following Subcutaneous Administration

Abstract: Hydrogels that can be injected into the body using standard needles or catheters enable a minimally invasive strategy to prolong local delivery of therapeutic drug and cellular cargo. In particular, physically crosslinked hydrogels exhibit shear-thinning and self-healing behaviors enabling facile injectability and depot formation upon administration. While prior efforts to characterize these systems have focused on injectability and cargo release behaviors, prediction of cargo release in the body often assumes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Previous work has shown that PNP hydrogels are biocompatible and are cleared from the subcutaneous space within several weeks, depending on the formulation and injection volume. 31,50…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that PNP hydrogels are biocompatible and are cleared from the subcutaneous space within several weeks, depending on the formulation and injection volume. 31,50…”
Section: Resultsmentioning
confidence: 99%
“…49 Finally, the yield stress of each formulation was determined to assess the ability of the depot to retain its shape under the forces present the site of injection; it has previously been demonstrated that yield stress is an important rheological property for subcutaneous depot formation and retention. 34,50 Yield stresses of 70 and 350 Pa were measured for the 1:5 and 2:10 formulations, respectively (Figure 2e). Again, previous work has shown that increasing nanoparticle content results in higher yield stress values.…”
Section: Rheological Characteristics Of the Pnp Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…We characterized the rheological properties of PNP hydrogels prepared with and without bimatoprost to ensure the drug cargo does not interfere with the critical properties for injectability and depot formation ( Figure 2b-e ). [17, 20] Frequency-dependent oscillatory shear rheology showed that the frequency responses of the materials were unchanged with encapsulation of bimatoprost. Indeed, both formulations showed robust solid-like properties across the entire range of timescales evaluated, evident from the storage modulus G’ being larger than the loss modulus G’’ ( Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…[17] It is also important that this material recovers it’s mechanical properties rapidly following injection to limit drug burst release and form a robust depot for extended release. [20] To assess the self-healing of our materials, we applied consecutive periods of high (10 rad s −1 ) and low (1 rad s −1 ) stress to the hydrogel formulations and observed drops in viscosity at high stress and rapid recovery of the material properties at low stress over several cycles, indicating the high stress disrupts the non-covalent PNP interactions responsible for crosslinking in these systems, and these interactions reform once the stress is removed ( Figure 2e ). To further evaluate injectability of the PNP gels, we fit the steady shear flow rheology data with the power law , which relates viscosity (η) and shear rate for non-Newtonian complex fluids, and extracted values for the consistency index ( K ) and shear-thinning parameter ( n ).…”
Section: Resultsmentioning
confidence: 99%